POSITIVE TRENDS IN THE NUMBER OF NURSES AND TECHNICIANS IN MONTENEGRO: AN OVERVIEW OF 2014–2023 - Šćepanović, Lidija; Vujošević, Zoran (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Achieving universal health coverage is a major challenge for all countries, and progress largely depends on the resources they possess and their availability. The aim of the paper is to review the provision and dynamics of the number of nurses/technicians and their structure in the ten-year period 2014–2023, as well as to examine whether there was a change in the equity of their distribution in relation to the number of inhabitants across municipalities.Methodology: A retrospective analysis of data on nurses employed in public health institutions in Montenegro for the period 2014–2023 was conducted, focusing on the following outcomes: the longitudinal increase in the number of nurses, the nurse-to-doctor ratio, the distribution of nurses by sex, age, and education, and the Gini coefficient as a measure of inequality in the distribution of nurses in relation to the population across municipalities.Results: The density of nursing personnel increased by 24% between 2014 and 2023, reaching 5.84 per 1,000 inhabitants in 2023, while the nurse-to-doctor ratio in the system reached 2.04:1. Nurses are predominantly female, aged 35–44, and the share of male nurses is increasing (12.91 in 2014 compared to 18.68 in 2023). One-fifth of the nurses have completed a college or university education. The Gini coefficient of inequality of distribution of nurses/technicians decreased from 0.195 in 2014. to 0.191 in 2023.Conclusion: In the last ten years, there have been significant positive changes in the density and structure of nurses which have probably been influenced by the health policy measures implemented during the COVID-19 pandemic.
Keywords: nurses; health workforce; health policy